Research regulatory compliance - Suckow, Mark A.; Yates, Bill J. (London : Academic Press is an imprint of Elsevier, 2015)
Research Regulatory Compliance offers the latest information on regulations and compliance in the laboratory. With the increasing complexity of regulations and need for institutional infrastructure to deal with compliance of animal use issues, as well as a requirement surrounding human subjects, this publication provides reputable guidance and information. The book is extremely helpful as a resource for researchers, administrators, and technicians in the laboratory, and is also a great asset for faculty or new researchers coming in to the laboratory environment. It will help prepare users for the deluge of regulatory and compliance issues they will face while conducting their scientific programs. The book is edited and authored by known leaders in the field of compliance and regulations, and contains extensive research on the topics. It represents the new standard for information in every laboratory.
Online resource; title from PDF title page (Ebsco, viewed June 18, 2015).
Includes bibliographical references and index.
Keywords: Research -- Government policy -- United States; Research -- Moral and ethical aspects; Medicine -- Research -- Moral and ethical aspects; Laboratories -- Management; SCIENCE -- Research & Methodology; Laboratories -- Management; Medicine -- Research -- Moral and ethical aspects; Research -- Government policy; Research -- Moral and ethical aspects; United States; Research -- standards; Research -- legislation & jurisprudence; United States; Electronic books; Electronic books